2012
DOI: 10.1371/journal.pone.0038763
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Effects of Biological Invasions: Cellular and Physiological Responses of Fish Eating the Exotic Pest Caulerpa racemosa

Abstract: The green alga Caulerpa racemosa var. cylindracea has invaded Mediterranean seabed including marine reserves, modifying the structure of habitats and altering the distributional patterns of associated organisms. However, the understanding of how such invasion can potentially affect functional properties of Mediterranean subtidal systems is yet to be determined. In this study, we show that C. racemosa changes foraging habit of the native white seabream, Diplodus sargus. In invaded areas, we found a high frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 76 publications
4
50
0
Order By: Relevance
“…In this respect, it is worth noting that the harmful indole alkaloid caulerpin, produced by both the aquarium strain of C. taxifolia and by C. cylindracea, which is directly responsible for detrimental biological effects on native Mediterranean fauna (e.g. Felline et al, 2012), was not observed in Ctvd collected in its area of origin (Waterhouse Island, Australia) (Schwede et al, 1986). If confirmed for the Mediterranean populations, the absence of caulerpin might imply further biological differences between the two C. taxifolia alien strains, which might in turn correspond to different ecological effects on the resident biota.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is worth noting that the harmful indole alkaloid caulerpin, produced by both the aquarium strain of C. taxifolia and by C. cylindracea, which is directly responsible for detrimental biological effects on native Mediterranean fauna (e.g. Felline et al, 2012), was not observed in Ctvd collected in its area of origin (Waterhouse Island, Australia) (Schwede et al, 1986). If confirmed for the Mediterranean populations, the absence of caulerpin might imply further biological differences between the two C. taxifolia alien strains, which might in turn correspond to different ecological effects on the resident biota.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the same studies [50,51] the exposure to the alga was also demonstrated to induce a) alteration of the activity of the Na + -K + -ATPase, which is responsible for the electrochemical gradient across the plasma membrane and it is critical for the osmotic balance of the cell, the resting membrane potential, and the excitable properties of muscle and nerve cells [54][55][56][57][58], b) neurotoxic effects, documented by acetylcholinesterase inhibition, and c) changes in the morphology of gonads. The observed alterations may cause detrimental health status and altered behaviour in the fish, potentially preventing the reproductive success of fish population [51].…”
Section: Biomarkers As Useful Tool For Detecting Subtle Effects Of Bimentioning
confidence: 72%
“…Besides its application in chemical pollution monitoring and assessment, recently the usefulness of the biomarker approach has been demonstrated also for the detection of the impact of alien species in marine environments [50,51]. Alien species can cause severe changes in the ecosystem's functioning and are recently recognized as principal agents of global change [52].…”
Section: Biomarkers As Useful Tool For Detecting Subtle Effects Of Bimentioning
confidence: 99%
See 2 more Smart Citations